Wearable technologies, brand community and the growth of a transhumanist vision. Issue 5 (24th March 2022) - Akdevelioglu, Duygu; Hansen, Sean; Venkatesh, Alladi
ABSTRACT: By enabling users to digitally monitor their health and behaviour, wearable technologies foster the perspective of the quantified self, a cultural phenomenon emphasising personal improvement through self-tracking. This vision, in turn, provides a basis for new forms of social engagement. In this netnographic study, we explore a brand community for users of the Fitbit wearable device. Our analysis reveals two structural dynamics – material agency and quantitative anchoring – which create a foundation for what we label 'accidental transhumanism', a transitional movement towards a transhumanist vision based on self-quantification, self-extension, and integration with technology. We further highlight the social engagement mechanisms, including motivating empowerment, friendly rivalry, and trusting engagement, that are built upon this foundation. Leveraging these findings, we theorise a novel model of the interaction of consumers and system artefacts in socio-technical assemblages. We refer to this novel phenomenon of brand community centred on self-quantification as quantified self-in-community, and consider both the beneficial and potentially deleterious impacts that it presents.